Generation of influenza A viruses as live but replication-incompetent virus vaccines - Si, Longlong; Xu, Huan; Zhou, Xueying; Zhang, Ziwei; Tian, Zhenyu; Wang, Yan; Wu, Yiming; Zhang, Bo; Niu, Zhenlan; Zhang, Chuanling; Fu, Ge; Xiao, Sulong; et al. (Science (American Association for the Advancement of Science), 2016)
The conversion of life-threatening viruses into live but avirulent vaccines represents a revolution in vaccinology. In a proof-of-principle study, we expanded the genetic code of the genome of influenza A virus via a transgenic cell line containing orthogonal translation machinery. This generated premature termination codon (PTC)-harboring viruses that exerted full infect i vi ty but were replication-incompetent in conventional cells. Genome-wide optimization of the sites for incorporation of multiple PTCs resulted in highly reproductive and genetically stable progeny viruses in transgenic cells. In mouse, ferret, and guinea pig models, vaccination with PTC viruses elicited robust humoral, mucosal, and T cell-mediated immunity against antigenically distinct influenza viruses and even neutralized existing infecting strains. The methods presented here may become a general approach for generating live virus vaccines that can be adapted to almost any virus.